KURIKULUM MERDEKA DALAM MEMPERSIAPKAN GENERASI DIGITAL NATIVES - Jannah, Raudhotul; Usmaulida Rahimullah; Nurhizrah Gistituati; Hadiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In a rapidly evolving digital era, a younger generation called ‘digital natives’ have grown up with technology influencing the way they interact and learn. The Merdeka Curriculum, launched by Indonesia's Ministry of Education, Culture, Research and Technology in 2022, aims to adapt education to the needs of this generation. It emphasises the development of 21st century competencies, including critical thinking, creativity, collaboration and communication (4Cs), as well as digital literacy which includes understanding and using technology safely and effectively. This research uses the literature review method to analyse the relevance of Merdeka Curriculum in preparing a generation of digital natives. The literature reviewed includes various sources from academic databases and trusted institutional reports, focusing on education, technology, and developmental psychology. The results of the analysis show that Merdeka Curriculum integrates technology in learning, encourages project-based learning, and personalisation to suit the preferences of digital natives. Nonetheless, the implementation of this curriculum faces challenges such as the digital divide and teacher readiness. The government needs to improve infrastructure, teacher training and community support to overcome these challenges. In conclusion, Merdeka Curriculum has significant potential in preparing students for success in the digital era, both locally and globally. It not only aims to improve digital skills, but also develops character and human values, preparing students to become reflective and ethical global citizens.